THE EFFECT OF MUSIC ON FREE THROW PERFOMANCE WHEN PLAYING BASKETBALL - Tony Wibowo; Jeremy Riantono (Universitas Internasional Batam, 2022)
This study was conducted to find out how music affects basketball free throw performance. The influence of music in free throws is considered important for building tension and adrenaline in a match, and it is rarely reported in the scientific method how music in free throws affects players. This study uses qualitative methods using experimental methods. This free throw experiment used four parameters and four changes in musical tempo, and each parameter consisted of 30 participants. The parameters we use are in and out of the ball, using scoring, pre-shot time, and time during the shooting phase. Experimental results show that music can have a positive impact on free throw performance. Music has significantly impacted performance in free throws which require good tension and adrenaline